2007
DOI: 10.1063/1.2800038
|View full text |Cite
|
Sign up to set email alerts
|

Transient deformation and drag of decelerating drops in axisymmetric flows

Abstract: Transient deformation and drag coefficients of decelerating drops in axisymmetric flows are numerically computed. The drag coefficients are compared with those of solid spheres. In the case of drops, the behavior of the drag coefficient is dependent on the deformation and internal circulation of the drops in addition to the factors which are important for solid spheres. These, in turn, are dependent on the gas-based Weber number (Weg) and the Ohnesorge number (Ohl). At the relatively low Weg of 1, when the def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 58 publications
6
25
0
Order By: Relevance
“…Maximum value of drag coefficient was also investigated for the range of Weber numbers investigated in this research and is shown in Table 1. If the value of maximum drag coefficient is linearly extrapolated for We = 10, we obtain a value of 2.58, which agrees closely with the value obtained by Wadhwa et al (2007). The decreasing trend of the maximum and average drag coefficient was also observed in experiments conducted by Warnica et al (1995), although the Weber numbers studied during their experiments were very low.…”
Section: Time Averaged Drag Coefficient Of Deforming and Fragmenting supporting
confidence: 76%
“…Maximum value of drag coefficient was also investigated for the range of Weber numbers investigated in this research and is shown in Table 1. If the value of maximum drag coefficient is linearly extrapolated for We = 10, we obtain a value of 2.58, which agrees closely with the value obtained by Wadhwa et al (2007). The decreasing trend of the maximum and average drag coefficient was also observed in experiments conducted by Warnica et al (1995), although the Weber numbers studied during their experiments were very low.…”
Section: Time Averaged Drag Coefficient Of Deforming and Fragmenting supporting
confidence: 76%
“…Thus they proposed the sheet-thinning mechanism verified also by numerical studies mentioned latter in this section (Han and Tryggvason, 2001;Khosla and Smith, 2006;Wadhwa et al, 2007). Recently, (Opfer et al, 2012;Opfer et al, 2014) studied experimentally and theoretically the bag breakup of droplets under a continuous air jet flow.…”
Section: ) Among Others)mentioning
confidence: 72%
“…Later (Quan, 2009) used the same model to examine the interaction between two impulsively accelerated droplets as a function of the distance between them. (Wadhwa et al, 2007) Recently, (Yang et al, 2016) used a variant of the CLSVOF methodology to study the effect of density ratio (ε=10-60) on the droplet breakup for a high We number of 225.…”
Section: ) Among Others)mentioning
confidence: 99%
“…Traditionally, there exist five distinct regimes that are well established in the literature (Pilch & Erdman 1987;Guildenbecher, López-Rivera & Sojka 2009). They are, axisymmetric (Han & Tryggvason 2001;Aalburg, Leer & Faeth 2003;Wadhwa, Magi & Abraham 2007;Chang, Deng & Theofanous 2013) approximations. Additionally, fluid density ratios are often assumed to be small, or the fluids are considered to be incompressible (Han & Tryggvason 2001;Aalburg et al 2003;Quan & Schmidt 2006;Jalaal & Mehravaran 2014;Xiao, Dianat & McGuirk 2014;Castrillon Escobar et al 2015;Jain et al 2015).…”
Section: Introductionmentioning
confidence: 99%